The impact of climate change on population urbanization: Evidence from china - Chai, Kuang-Cheng; Ma, Xin-Rui; Yang, Yang; Lu, Yu-Jiao; Chang, Ke-Chiun (Frontiers in Environmental Science, 2022)
Climate change, which is mainly caused by carbon emissions, has attracted attention worldwide. With the continuous increase in temperature, the urban heat island effect, extreme weather, and water shortages have seriously affected the urbanization process. Through an empirical analysis of panel data from 28 provinces in China from 2006 to 2018, this study examines the impact of climate change-induced temperature changes on the urbanization of China's population. The results show that the urbanization level has a significant double-threshold effect on the impact of temperature on urbanization. When the urbanization level crosses the corresponding threshold value, the negative impact of temperature on urbanization is relatively weak. Understanding the impact of climate change on urbanization has become increasingly important as climate warming increases. On the one hand, the climate issue has always been a topic of common concern around the world. On the other hand, studying how climate change affects population urbanization is conducive to identifying the human factors that affect climate change and proposing corresponding solutions. Simultaneously, it also provides a reference for optimizing the distribution of urban and rural populations, and can comprehensively consider the relationship between climate change and urbanization in the formulation and implementation of policies. On this basis, the Chinese government should strengthen financial support for climate change, play a leading role in policies, improve the urban layout and structure, and increase the resilience of cities to climate change.